Improving maternal and PeRinatal Outcomes aMong wOmen with and without obEsity (PROMOTE): protocol for a prospective pregnancy cohort study - Tim Usherwood; Victoria Flood; Ngai Wah Cheung; Dharmintra Pasupathy; Ya Wang; Ben J Smith; Judith Heads; Mark McClean; Sarah Melov; James Elhindi; Justin McNab; Adrienne Kirby; et al. (BMJ Open)
Introduction The Improving maternal and PeRinatal Outcomes aMongst wOmen with and without obEsity (PROMOTE) cohort study is a prospective pregnancy cohort study that seeks to test current assumptions and understanding of cardiometabolic disease and risk during pregnancy. The demographic shift among pregnant women, including older age and increasing obesity, has resulted in an increased risk of cardiometabolic complications during pregnancy and over the lifetime for mother and offspring. Unfortunately, lifestyle interventions during pregnancy have not yet produced clinically meaningful outcomes. Furthermore, cohort studies in pregnancy are costly and have selection bias due to study burden and attrition. There is an urgent need for high-quality observational data collected pragmatically about cardiometabolic health and determinants during pregnancy, to identify subgroups at highest risk and to provide rich contextual information around the interplay of clinical and social determinants.Methods and analysis The PROMOTE cohort study is a prospective pregnancy cohort study recruiting pregnant participants <16 weeks’ gestation at a large urban public teaching hospital with high social and cultural diversity in Sydney, Australia. Participants are surveyed about their physical activity levels, dietary quality, emotional well-being and sociodemographic status using validated tools. Participants are consented for biobanking and for use of routinely collected clinical and social data, including medical conditions, body mass index, blood pressure and glycaemia. Follow-up is from routinely collected data. Pregnancy and birth outcomes include maternal and neonatal pregnancy and birth outcomes include gestational diabetes mellitus, hypertensive disorders of pregnancy and preterm birth. Postnatal and longitudinal data collection is planned.Ethics and dissemination The study has been approved by the Western Sydney Local Health District Human Research Ethics Committee (2021/ETH00287). The study will disseminate results by academic publication, conference presentations and targeted implementation partnerships.Trial registration number Retrospectively registered with the Australian New Zealand Clinical Trials Registry (registration number: ACTRN12624001344583).